Creative translation practices in the transmedia space - challenges in the translation of cross-media projects - Rajchelt, Balbina (Free your mind: Reflections on language, literature and culture, 2022)
The modern entertainment industry is growing rapidly and is creating an ever-larger body of media to meet the growing demand from consumers, readers, viewers and gamers. In our modern, digital and global society, it is especially important that screenwriters, directors and video game designers make their work accessible to as many audiences as possible. Of course, this is only possible if these works can be translated into other languages to present them to new linguistic and cultural groups. However, translating multimedia works such as movies, video games, theater performances etc. brings with it many new challenges, not least because most of these projects no longer function as standalone works but rather belong to larger multimedia franchises. A translator dealing with such a work must not only pay attention to the purely linguistic and cultural context of the text; The technical limitations of the medium and any legal requirements must also be observed. Moreover, the new text must match those already established in the series, so the translator's freedom of choice of words and style is often severely restricted. Another challenge is the way many translations of transmedia texts work, where (especially in the case of texts from video games) the translator does not receive the entire text, but only single fragments of text, paragraphs, phrases, or even individual words, without access to the context. The aim of this article is to show how creative translation practices – especially transcreation, trans-adaptation and cultural translation – and the use of technological tools can be used to translate transmedia projects so that translations meet the expectations of authors and audiences.